Institutions and the environment: with the introduction of Bob Jessop - Ostrom, Elinor (Journal of Public Governance, 2013)
In her article, Elinor Ostrom offers a critical account of a number of empirical studies, game-theoretic analyses and her own experiments in institutional design as applicable to the issue of overexploitation of common-pool resources. She argues that, given people’s ability to communicate, experiment and modify institutional rules, they can develop various – not necessarily market-based – solutions with a view to achieving sustainable management of such resources to which the concept of the tragedy of the commons supposedly applies.